Pengaruh Gaya Kepemimpinan,Stres Kerja Dan Motivasi Terhadap Kinerja Karyawan Pt.Pos Indonesia Kantor Pos Karanganyar - Aristiana, Rismaya Intan, Drs. Ma'ruf, MM (2016)
The purpose of this study was to determine the effect of leadership style, job stress and motivation on employee performance PT.POS INDONESIA karanganyar post office. In this research has the objective to analyze the influence of leadership , the performance of employees, the effect of work stress on employee performance and motivation influence on employee performance. In this test sampling with random sampling techniques, data types and sources of data used in this study using primary data obtained from the respondents' answers in the form of filling the questionnaire of employee PT.POS INDONESIA karanganyar post office. The test instrument used to test the feasibility of a question is Test Validity and Test Reliability. For the method of data analysis used in this study, the authors used multiple analysis reinforced with Normality Test, Test Multicollinearity, F test and t test that shows that all independent variables positive and significant effect on the dependent variable. Given this research can be concluded that employees of PT. POS INDONESIA karanganyar post office need leadership , job stress and motivation in improving employee performance